2019
DOI: 10.3390/nu11051061
|View full text |Cite
|
Sign up to set email alerts
|

Sea Cucumber (Stichopus japonicas) F2 Enhanced TRAIL-Induced Apoptosis via XIAP Ubiquitination and ER Stress in Colorectal Cancer Cells

Abstract: Natural products have shown great promise in sensitizing cells to TNF-related apoptosis-inducing ligand (TRAIL) therapy. Sea cucumber (SC) extracts possess antitumor activity, and hence their potential to sensitize colorectal cancer (CRC) cells to TRAIL therapy was evaluated. This study used Western blotting to evaluate the combination effects of SC and TRAIL in CRC, and determined the molecular mechanism underlying these effects. SC fractions and TRAIL alone did not affect apoptosis; however, combined treatme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(12 citation statements)
references
References 40 publications
1
11
0
Order By: Relevance
“…20 A variety of chemotherapeutic agents can block the cell cycle of tumor cells and enhance their sensitivity to TRAIL-induced apoptosis. [21][22][23] Since knockdown of cyclinB1 induced cell cycle arrest, we sought to determine whether it would contribute to TRAIL-induced apoptosis in HCC. Our study certified that knockdown of cyclinB1 sensitized HCC cells to TRAIL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…20 A variety of chemotherapeutic agents can block the cell cycle of tumor cells and enhance their sensitivity to TRAIL-induced apoptosis. [21][22][23] Since knockdown of cyclinB1 induced cell cycle arrest, we sought to determine whether it would contribute to TRAIL-induced apoptosis in HCC. Our study certified that knockdown of cyclinB1 sensitized HCC cells to TRAIL-induced apoptosis.…”
Section: Discussionmentioning
confidence: 99%
“…A previous study suggested that the inhibitory mechanisms of TRAIL in colon cancer included promotion of apoptosis and lymphocyte infiltration, as well as the inhibition of invasion and migration (14). To identify a successful cancer treatment method using TRAIL-R agonists, a variety of chemical compounds or natural products have been evaluated for their efficacies and mechanisms in sensitizing cancer cells to TRAIL-induced apoptosis (18)(19)(20). Kim et al (18) reported that sea cucumber enhanced TRAIL-mediated apoptosis by increasing proteasomal degradation of X-linked inhibitor of apoptosis protein (XIAP) and activating endoplasmic reticulum stress in CRC.…”
Section: Introductionmentioning
confidence: 99%
“…To identify a successful cancer treatment method using TRAIL-R agonists, a variety of chemical compounds or natural products have been evaluated for their efficacies and mechanisms in sensitizing cancer cells to TRAIL-induced apoptosis (18)(19)(20). Kim et al (18) reported that sea cucumber enhanced TRAIL-mediated apoptosis by increasing proteasomal degradation of X-linked inhibitor of apoptosis protein (XIAP) and activating endoplasmic reticulum stress in CRC. Another study reported that icariin, a chemical compound classified as a prenylated flavonol glycoside, sensitized colon cancer cells to TRAIL-induced apoptosis through reactive oxygen species-, ERK-and CCAAT enhancer-binding protein homologous protein-mediated modulation of death receptor (DR)-4 and -5 expression (19).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Sea cucumber is a widely used traditional Chinese medicine (TCM) with numerous healthy benefits (13). It is rich in a variety of bioactive components, such as polysaccharide, polypeptide and saponins (13)(14)(15)(16). Sea cucumber fucoidan has been reported to have anticoagulant, anti-hyperglycemic, anti-inflammatory, and immunomodulatory activity (17)(18)(19).…”
Section: Introductionmentioning
confidence: 99%